2012
DOI: 10.7150/jca.3042
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Malignancy after Living Kidney Transplantation: A Multicenter Study from Iran

Abstract: Malignancy is a common complication after renal transplantation. However, limited data are available on post-transplant malignancy in living kidney transplantation. Therefore, we made a plan to evaluate the incidence and types of malignancies, association with the main risk factors and patient survival in a large population of living kidney transplantation. We conducted a large retrospective multicenter study on 12525 renal recipients, accounting for up to 59% of all kidney transplantation in Iran during 22 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
2
23
0
2
Order By: Relevance
“…Squamous cell carcinoma of the skin is the most common malignancy and affected patients have a five-fold increased risk of developing another solid tumor ( 31 ). In European population, posttransplant lymphoproliferative disorders (PTLD) are the second most common malignancies and the same features were founded in a report from Iran ( 32 - 34 ). Geographic distribution of human herpes virus type-8 and Epstein-Bar virus (EBV) infections are important risk factors for Kaposi sarcoma and PTLD development, respectively ( 33 , 34 ).…”
Section: Resultsmentioning
confidence: 70%
“…Squamous cell carcinoma of the skin is the most common malignancy and affected patients have a five-fold increased risk of developing another solid tumor ( 31 ). In European population, posttransplant lymphoproliferative disorders (PTLD) are the second most common malignancies and the same features were founded in a report from Iran ( 32 - 34 ). Geographic distribution of human herpes virus type-8 and Epstein-Bar virus (EBV) infections are important risk factors for Kaposi sarcoma and PTLD development, respectively ( 33 , 34 ).…”
Section: Resultsmentioning
confidence: 70%
“…It has been demonstrated that the immune surveillance plays a fundamental role in the pathogenesis of melanoma (4), as confirmed by the importance of immunotherapeutic approach in the treatment of advanced stages of this disease (9). However, while data concerning the higher risk of NMSC after transplantation are well established (2, 3, 10), not all authors agree about the increase in melanoma risk in transplant recipients (1,(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Although immunosuppressive therapy has successfully reduced the risk of rejection after kidney transplantation, more aggressive immunosuppression has increased the occurrence of malignancy and PTLD 1 , 2 , 14 . Renal transplant recipients with PTLD have been managed with a variety of approaches including reduction in immunosuppression, antiviral therapy, surgical resection, chemotherapy, radiation and cellular therapy 2 , 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive therapy in kidney transplant recipients have successfully reduced the risk of rejection after kidney transplantation, however, malignancy and post-transplant lymphoproliferative disorder (PTLD) are common complications of immunosuppressive therapy 1 5 .…”
Section: Introductionmentioning
confidence: 99%